Measuring the dose in bone for spine stereotactic body radiotherapy. (April 2021) - Shaw, Maddison; Lye, Jessica; Alves, Andrew; Hanlon, Maximilian; Lehmann, Joerg; Supple, Jeremy; Porumb, Claudiu; Williams, Ivan; Geso, Moshi; Brown, Rhonda
Highlights: Anthropomorphic phantoms with synthetic bone allow clinically realistic end-to-end testing. Monte Carlo simulations provide corrections for measuring dose in bony materials. Dose-to-medium and dose-to-water scenarios require corrections ranging from 0.7 to 12.5%. Algorithm specific corrections improved results of 63 SBRT spine dosimetry audit plans. Abstract: Purpose: Current quality assurance of radiotherapy involving bony regions generally utilises homogeneous phantoms and dose calculations, ignoring the challenges of heterogeneities with dosimetry problems likely occurring around bone. Anthropomorphic phantoms with synthetic bony materials enable realistic end-to-end testing in clinical scenarios. This work reports on measurements and calculated corrections required to directly report dose in bony materials in the context of comprehensive end-to-end dosimetry audit measurements (63 plans, 6 planning systems). Materials and methods: Radiochromic film and microDiamond measurements were performed in an anthropomorphic spine phantom containing bone equivalent materials. Medium dependent correction factors, kmed, were established using 6 MV and 10 MV Linear Accelerator Monte Carlo simulations to account for the detectors being calibrated in water, but measuring in regions of bony material. Both cortical and trabecular bony material were investigated for verification of dose calculations in dose-to-medium (Dm, m ) and dose-to-water (Dw, w ) scenarios. Results: For Dm, m calculations, modelled correction factors for cortical and trabecular bone in film measurements, and for trabecular bone in microDiamond measurements were 0.875(±0.1%), 0.953(±0.3%) and 0.962(±0.4%), respectively. For Dw, w calculations, the corrections were 0.920(±0.1%), 0.982(±0.3%) and 0.993(±0.4%), respectively. In the audit, application of the correction factors improves the mean agreement between treatment plans and measured microDiamond dose from −2.4%(±3.9%) to 0.4%(±3.7%). Conclusion: Monte Carlo simulations provide a method for correcting the dose measured in bony materials allowing more accurate comparison with treatment planning system doses. In verification measurements, algorithm specific correction factors should be applied to account for variations in bony material for calculations based on Dm, m and Dw, w .